Comparing Scientific Registry of Transplant Recipient posttransplant program-specific outcome ratings at listing with subsequent recipient outcomes after transplant - Wey, Andrew (Am J Transplant, 2018)
To improve accessibility of program-specific reports to patients, the Scientific Registry of Transplant Recipients released a 5-tier system for categorizing 1-year posttransplant program evaluations. Whether this system predicts subsequent posttransplant outcomes at the time patients are wait-listed has been questioned. We investigated the association of tier at listing and the corresponding continuous score used for tier assignment, which ranges from 0 (poor outcomes) to 1 (good outcomes), with eventual 1-year posttransplant graft survival for candidates listed July 12, 2011-June 16, 2014, who underwent transplant before December 31, 2016. One additional tier at listing was associated with better 1-year posttransplant outcomes in liver (hazard ratio [HR], (0.89)0.93(0.97)) and lung transplantation (HR, (0.84)0.90(0.97)), but not kidney (HR, (0.92)0.96(1.01)) or heart transplantation (HR, (0.93)1.02(1.10)). In liver and lung transplantation, longer time between listing and transplant was associated with stronger protective effects for high-tier programs. In kidney, liver, and lung transplantation, posttransplant evaluations at listing had non-linear associations with eventual posttransplant outcomes: relatively flat for 5-tier scores below 0.5 and decreasing for scores above 0.5. After adjusting for measured recipient and donor risk factors, posttransplant evaluations at listing predicted differences in eventual outcomes in liver and lung transplantation, providing useful information to patients.